31.1 COMBINING EXERCISE PHYSIOLOGY, RECREATIONAL THERAPY, VIRTUAL REALITY GAMING TECHNOLOGY, AND PSYCHOSOCIAL REHABILITATION TO PROMOTE PHYSICAL EXERCISE IN SERIOUS MENTAL ILLNESS. (9th April 2019) - Choi, Jimmy; Taylor, Beth; Fiszdon, Joanna; Astur, Robert; Haber, Lawrence; Shagan, Dana; Tek, Cenk; Kurtz, Matthew; Pearlson, Godfrey
Abstract: Background: Physical exercise (PE) is a safe, non-stigmatizing, and side-effect free intervention that has the potential to mitigate neurocognitive dysfunction in psychosis, as well as reduce anxiety and paranoia. Developing and promoting PE programs for people with SMI in the community where participants cannot be paid to participate requires an interdisciplinary approach to activate motivation for exercise. We report the initial development and pilot results of a PE community program developed to enhance motivation and engagement in adults with schizophrenia, merging expertise from the fields of exercise physiology, recreational therapy, virtual reality (VR) gaming technology, and neuropsychiatric rehabilitation. Methods: Adult outpatients diagnosed with schizophrenia (N=29) were enrolled in 18 hours (40 min session, 3x/week for 3 months) of exergaming. Exergaming uses interactive exercise equipment connected to a computer and monitor so the patient is engaged in a virtual game while exercising. For example, while pedaling on an exergaming stationary bike, the can have the experience of racing or biking through the countryside, either using a virtual reality headset or simply looking at the monitor. The PE regimen was tailored for each participant based on input from a (1) exercise physiologist about optimal methods to achieve volitional exhaustion and reduce the risk for injury, (b) recreational therapist who set up the overall exercise milieu to promote enjoyment, (c) expert in VR technology who calibrated and tailored the virtual experience to each participant (d) psychiatrist who monitored medical risk for strenuous exercise, and (d) psychologist who collected outcome data. Cognition and symptoms were assessed at baseline and post (3 mo.) while motivation and treatment engagement were recorded biweekly. Results: Large effects were seen in working memory from baseline to post (WASI WMI; ES=.53), with medium effects in overall symptoms (PANSS; ES=.30). Importantly, participants reported a high degree of motivation for PE throughout the treatment period (Intrinsic Motivation Inventory total score>35), and 27 out of 29 completed the entire PE regimen of 18 hours although they were not paid to attend. Conclusions: This study highlights the potential benefits of a PE program developed by an interdisciplinary team combing expertise in exercise, technology, recreation, and neuropsychiatry. Drawing from experience in other fields may help develop new treatments in psychiatric rehabilitation to maximize overall outcome. Funded by a Hartford Hospital Auxiliary Special Projects Grant to JC